RELATIONSHIP BETWEEN LANGUAGE LEARNING STRATEGIES AND ACHIEVEMENT WITH LEARNING MOTIVATION AMONG STUDENTS OF CHINESE AS FOREIGN LANGUAGE PROGRAMME IN MALAYSIA - Leong Chew Moi; Umi Kalsum Mohd Salleh; Chew Fong Peng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In Malaysia, teaching Chinese as a foreign language began in 1963 and has grown in popularity. Language Learning Strategies, or the measures students take to increase their learning, are critical to the final success of Chinese as a Foreign Language. Student achievement is determined by the application of language learning methods. Learning motivation, on the other hand, has a significant impact on academic achievement. This study’s purpose is to (1) investigate the level of Language Learning Strategy, Learning motivation, and Language Learning achievement. (2) To investigate the relationship between Language Learning Strategy and Language Learning achievement; (3) To investigate the relationship between Language Learning Strategy and Learning motivation; and (4) To investigate the relationship between Learning Motivation and Language Learning Achievement among students of the Chinese as a Foreign Language programme in Malaysia. The collected data were analysed quantitatively using SPSS for descriptive analysis and the relationship between language learning strategies, learning motivation, and achievement. The Pearson correlation analysis showed the highly correlated between language learning strategies, learning motivation, and achievement.